Introduction of Research Articles in Applied Linguistics by Indonesian and English Academics - UDI SAMANHUDI (Indonesian Research Journal in Education |IRJE|, 2017)
This study was an exploratory study focusing on the textual analysis of the rhetorical structure of ten preliminary samples of research article introductions (five research article introductions for each) in the area of applied linguistics written by Indonesian and English academics. The analysis of ten research article introduction sections written by both Indonesian and English writers refers to the procedures as suggested by Dudley-Evans (1994). The results of analysis on rhetorical moves as suggested in the Create a Research Space (CARS) model proposed by Swales (1990) in the article journal introduction section of Indonesian and English writers. This study presented the results of analysis of the rhetorical structure as found in the ten Introduction sections of research articles written by Indonesian and English academics. In general, the results showed similarities in terms of Move structure in which all Moves (1, 2 and 3) are identified in the ten articles written by writers from the two different language backgrounds.